Evaluation of the national Cleanyourhands campaign to reduce Staphylococcus aureus bacteraemia and Clostridium difficile infection in hospitals in England and Wales by improved hand hygiene: four year, prospective, ecological, interrupted time series study. (3rd May 2012) - Stone, Sheldon Paul; Fuller, Christopher; Savage, Joan; Cookson, Barry; Hayward, Andrew; Cooper, Ben; Duckworth, Georgia; Michie, Susan; Murray, Miranda; Jeanes, Annette; Roberts, J; Teare, Louise; et al.
Abstract : Objective To evaluate the impact of the Cleanyourhands campaign on rates of hospital procurement of alcohol hand rub and soap, report trends in selected healthcare associated infections, and investigate the association between infections and procurement. Design Prospective, ecological, interrupted time series study from 1 July 2004 to 30 June 2008. Setting 187 acute trusts in England and Wales. Intervention Installation of bedside alcohol hand rub, materials promoting hand hygiene and institutional engagement, regular hand hygiene audits, rolled out nationally from 1 December 2004. Main outcome measures Quarterly (that is, every three months) rates for each trust of hospital procurement of alcohol hand rub and liquid soap; Staphylococcus aureus bacteraemia (meticillin resistant (MRSA) and meticillin sensitive (MSSA)) and Clostridium difficile infection for each trust. Associations between procurement and infection rates assessed by mixed effect Poisson regression model (which also accounted for effect of bed occupancy, hospital type, and timing of other national interventions targeting these infections). Results Combined procurement of soap and alcohol hand rub tripled from 21.8 to 59.8 mL per patient bed day; procurement rose in association with each phase of the campaign. Rates fell for MRSA bacteraemia (1.88 to 0.91 cases per 10 000 bed days) and C difficile infection (16.75 to 9.49 cases). MSSA bacteraemia rates did not fall. Increased procurement of soap was independently associated with reduced C difficile infection throughout the study (adjusted incidence rate ratio for 1 mL increase per patient bed day 0.993, 95% confidence interval 0.990 to 0.996; P<0.0001). Increased procurement of alcohol hand rub was independently associated with reduced MRSA bacteraemia, but only in the last four quarters of the study (0.990, 0.985 to 0.995; P<0.0001). Publication of the Health Act 2006 was strongly associated with reduced MRSA bacteraemia (0.86, 0.75 to 0.98; P=0.02) and C difficile infection (0.75, 0.67 to 0.84; P<0.0001). Trust visits by Department of Health improvement teams were also associated with reduced MRSA bacteraemia (0.91, 0.83 to 0.99; P=0.03) and C difficile infection (0.80, 0.71 to 0.90; P=0.01), for at least two quarters after each visit. Conclusions The Cleanyourhands campaign was associated with sustained increases in hospital procurement of alcohol rub and soap, which the results suggest has an important role in reducing rates of some healthcare associated infections. National interventions for infection control undertaken in the context of a high profile political drive can reduce selected healthcare associated infections.